Economic analysis and policy in underdeveloped countries - "Bauer, P.T." (London, 1957)
This volume is a re-issue of the published version of three lectures delivered in 1956 at the Commonwealth Studies Center of Duke University, and subsequently published in Great Britain by the Cambridge University Press. Within the general field of the economics of poor countries it discusses a number of specific topics under three main headings: the study of underdeveloped econ omies; aspects of their economic landscape; some issues of policy.
Keywords: Underdeveloped countries economic conditions